Adrián Torrealba Navas, Ibero-American Tax Law: Under the 2015 CIAT Model Tax Code, (Derecho Tributario Iberoamericano: A la luz de la versión 2015 del MCTCIAT), Instituto Colombiano de Derecho Tributario/Instituto Colombiano de Derecho Aduaneiro, 2017 - Hallivis Pelayo, Manuel Luciano (My University, 2018)
The year 2015 was pivotal in the evolution of Latin-American tax law, especially in light of the OECD/G20Base Erosion and Profit Shifting (BEPS) project; the 38thConference of the Latin American Tax Law Institute (Instituto Latinoamericano de Derecho Tributario) that took place in Mexico; and the consolidation of various tax reforms. Nevertheless, one of the most significant events was the publication of the CIAT Model Tax Code, which has proven to be a significant step forward in tax law research. Some scholars agree that the CIAT Model Tax Code is fundamental to help organize and apply all tax measures. Under the BEPS project, this statement is undoubtedly true. Indeed, as is the case with various other instruments such as the Commentary on the OECD Model Tax Convention (OECD Model), the CIAT Model Tax Code constitutes soft law and is basically aimed at Ibero-American tax administrations. However, as it has an impact on tax codes, which are laws governing the legal tax relationship, it is a document that should be taken into account by all tax professionals, be they accountants, lawyers, researchers, tax officials or judges.
Literature review: Adrián Torrealba Navas, Ibero-American Tax Law: Under the 2015 CIAT Model Tax Code, (Derecho Tributario Iberoamericano: A la luz de la versión 2015 del MCTCIAT)